Finite element analysis of low-profile reconstruction plates for atrophic mandibles: a comparison of novel 3D grid and conventional plate designs - Guerra, Raphael Capelli [UNESP]; de Fátima Borim Pulino, Bianca [UNESP]; Salomão Júnior, Vitor Floriano; dos Santos Pereira, Rodrigo; Thieringer, Florian M.; Sacco, Roberto; Sader, Robert; Vieira, Eduardo Hochuli [UNESP] (Springer Nature, 2024)
Objectives: This study aimed to compare the reconstruction with type 2.4 and three-dimensional (3D) grid plates relating the areas of weakness to anatomical regions of force incidence in atrophic mandibles with and without segmentation using finite element analysis (FEA). Materials and methods: Strength and force quality in the mandible were also determined. The atrophic mandible models with and without segmentation were divided into four groups, and the behavior of each plate was analyzed using finite element analysis. In the atrophic mandible without segmentation using the type 2.4 reconstruction plate, the highest stress concentration in the plate was observed in the posterior region of the mandibular body and in the grid type 3D reconstruction plate was observed in the mandibular angle. Results: In the segmented atrophic mandible with the 2.4 reconstruction plate, higher stress concentration was observed in the mandibular segment defect. Analysis of the 3D grid-like reconstruction plate revealed that the geometry of the plate conferred greater stiffness to the assembly, as the most significant stress concentration was observed at the mandibular angle. Conclusion: The width of the plate design may influence the strength, not the thickness.
Keywords: Edentulous mandible; Finite element analysis; Mandible; Mandible fixation technique; Mandibular reconstructions